Study on Presplitting Blasting the Roof Strata of Adjacent Roadway to Control Roadway Deformation - Xiaojie Yang; Chaowen Hu; Manchao He; Haohao Wang; Yubo Zhou; Xiaoyu Liu; Enze Zhen; Xingen Ma (Shock and Vibration)
In order to solve the problem of roadway deformation based on the theory of “short cantilever beam by roof cutting,” the method of “pressure relief by roof cutting in the adjacent roadway” is proposed. Through presplitting blasting the roadway hard rock layer, the stress propagation path is cut off, and the surrounding rock stress environment of the roadway is improved, to achieve the purpose of controlling the deformation of the roadway caused by stress. Through theoretical analysis, it is determined that the depth of the presplitting blasthole is 17 m, and the angle with the vertical direction is 10°. Based on in situ measurements and tests, by presplitting blasting the roof strata of the adjacent roadway, the maximal value of the working resistance of the hydraulic support in the presplitting blasting side of the working face decreased by 24.9%, and the average volumes of the maximum floor heave, the maximum roof subsidence, and the maximum ribs displacement were reduced by 50.1%, 34.9%, and 41.7%, respectively. This method completely changes the traditional thought patterns of “reinforcing support” to control roadway deformation from “strong support” to “pressure relief.” It provides a new idea for controlling the roadway deformation.